IL-17A contributes to propagation of inflammation but does not impair adipogenesis and/or insulin response, in adipose tissue of obese individuals. (February 2020) - Pestel, Julien; Chehimi, Marwa; Bonhomme, Mélanie; Robert, Maud; Vidal, Hubert; Eljaafari, Assia
Graphical abstract: Highlights: IL-17A does not play a major role in inflammation-mediated impairment of adipogenesis in human obese ASC. IL-17A does not play a major role in inflammation-mediated insulin resistance in obese ASC. IL-17A is involved in the propagation of inflammation within adipose tissues of obese subjects. Anti-IL17A should benefit to inflammatory diseases where obesity contributes to poorer response. IL-17A differentially regulates IL-17RA expression in human ASC versus MSC. Abstract: Background: Adipose tissue is infiltrated with various immune cells, including Th17 lymphocytes and monocytes/macrophages, in obese individuals. We have previously demonstrated the role of obese adipose-derived stem cells (ob-ASC) and adipocytes (AD) in the mediation of inflammation through promotion of Th17 cells and activation of monocytes. Such an inflammation resulted in impaired ob-ASC adipogenesis and AD insulin response. In the present study, we investigated the role of IL-17A in the impairment of these functions. Methods: With this aim, we used Secukinumab, a potent human anti-IL17A monoclonal antibody which has been approved for the treatment of some IL-17A related inflammatory diseases, notably Psoriasis. This antibody was added or not to phytohemagglutinin A-activated co-cultures of ob-ASC and mononuclear cells. The conditioning media of those co-cultures were harvested and added to AD ongoing differentiation from ob-ASC. Adipogenesis, insulin sensitivity and secretion of inflammatory cytokines were then measured using qRT-PCR, Western blots and ELISAs, respectively. Results: Surprisingly, we did not observe any direct effect of IL-17A on ob-ASC adipogenesis, despite sensitivity of ob-ASC to IL-17A. Moreover, IL-17A blockade, with the help of Secukinumab, did not lead to the recovery of adipogenesis and insulin response, when these functions were impaired by the presence of an inflammatory conditioning medium. However, the up-regulation of IL6 and IL1B mRNA expression by AD submitted to inflammatory conditioning medium was inhibited in the presence of Secukinumab, which indicates that IL-17A may play a role in the propagation of inflammation towards AD. In conclusion: we show herein that IL-17A does not play a major role in the impairment of adipogenesis and/or insulin resistance mediated by an inflammatory environment, but contributes to the propagation of inflammation in human obese adipose tissues. This suggests a beneficial effect of anti-IL17A mAb in inflammatory pathologies, where obesity contributes to poorer response to biologic treatments.